2009
DOI: 10.3386/w15390
|View full text |Cite
|
Sign up to set email alerts
|

Music for a Song: An Empirical Look at Uniform Song Pricing and its Alternatives

Abstract: With digital music as its context, this paper quantifies how much money would be made using alternatives to uniform pricing. Using survey-based data on nearly 1,000 students' valuations of 100 popular songs in early 2008 and early 2009, we find that various alternatives can raise both producer and consumer surplus. Digital music revenue could be raised by between a sixth and a third relative to profit-maximizing uniform pricing. While person-specific uniform pricing can raise revenue by over 50 per cent, none … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 18 publications
2
31
1
1
Order By: Relevance
“…My estimates are consistent with those of Shiller and Waldfogel (2011), who estimate the demand for iTunes songs using survey data collected from 500 students. They find that when the price of an iTunes song increases from $0.99 to $1.87, demand drops by 42% from 7434 to 4351.…”
Section: Music Demandsupporting
confidence: 78%
See 1 more Smart Citation
“…My estimates are consistent with those of Shiller and Waldfogel (2011), who estimate the demand for iTunes songs using survey data collected from 500 students. They find that when the price of an iTunes song increases from $0.99 to $1.87, demand drops by 42% from 7434 to 4351.…”
Section: Music Demandsupporting
confidence: 78%
“…I identified a similar price effect on demand for iTunes songs using the estimates in Table 8. When the price of an iTunes song was increased from $0.99 to $1.87 in the survey, demand drops 49%, which is reasonably close to the 42% in Shiller and Waldfogel (2011). At the same time, I also found a price effect on the demand for other types of music.…”
Section: Music Demandsupporting
confidence: 58%
“…analyzed if bundles of subscription television, …xed broadband and …xed voice are a relevant product market in the sense of competition policy, using consumer level data. Shiller and Waldfogel (2011) analyzed the welfare impact of various forms of pricing for the music industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Starting in 2009, the store moved to three tiers at $0.69, $0.99, and $1.29 (Apple 2009). Both theory (such as Bakos and Brynjolffson 1999) and empirical research on music (Shiller and Waldfogel 2011) had suggested the promise of more sophisticated pricing strategies for digital products, and there has been a move recently to bundled content through musicstreaming services. For example, Spotify, which offers bundled access to a wide variety of music, has grown from 0.5 million paid subscribers in 2010 to 50 million paid subscribers in March 2017 (see https://www.statista.com/statistics/244995/ number-of-paying-spotify-subscribers/).…”
Section: The Promise Of Bundled Sales Of Zero Marginal Cost Productsmentioning
confidence: 99%